Students' Perception on the Utilization of Language Laboratory for Speaking Performances - Aulia, Vivi (Journal of ELT, Linguistics, and Literature, 2017)
This article is a report of correlational research conducted to the second undergraduate English major in STKIP PGRI Banjarmasin. The objective of this research is to examine whether the students’ perception on the utilization of language laboratory in Speaking course correlate significantly with their speaking performances. The instruments used for collecting data are questionnaire and Speaking test. The result of this research shows that there is no significant correlation between them. The existence of students’ perception on the utilization of language laboratory in Speaking course does not influence and gives any valuable contribution to their speaking performances. There are extraneous and possible factors that may influence the result of this research. Finally, this research is expected to become the new perspective about language laboratory that can be utilized as interactive media or teaching aid in teaching Speaking course. Furthermore, exploring the extraneous factors that occur to students in this research is needed to be investigated widely.